Analysis of the Effect of Prices and Quality of Facilities on Tourist Visit Decision - Ayat Taufik Arevin (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the impact of price and facilities on tourists' visitation decisions. This focus is based on the importance of the tourism industry in enhancing regional economies, where price and facilities are key elements influencing tourists' decisions when selecting a destination. In the context of increasingly intense global competition, tourist destinations need to understand consumer preferences related to their perceptions of price and the quality of the facilities offered. The research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to visitors of Taman Mini Indonesia Indah (TMII). The sampling technique used was non-probability sampling with purposive sampling, resulting in 162 completed questionnaires. Data analysis was conducted using Structural Equation Modelling (SEM) with the aid of AMOS software to test the relationships between the variables of price, facilities, and visitation decisions. The results indicate that both price and facilities significantly influence tourists' visitation decisions. Specifically, facilities have a stronger impact compared to price on tourists' decisions to visit. These findings underscore the importance of competitive pricing strategies and the enhancement of facility quality in efforts to increase the attractiveness of tourist destinations.